Cytotoxicity mechanisms of passive anti-GD2 immunotherapy in pediatric tumors - M. E. Melnikov; S. A. Kulyova; G. V. Kondratiev; M. M. Vasilyeva; O. E. Savelieva (Успехи молекулярной онкологии)
Cells of neuroblastoma, soft tissue sarcomas, osteosarcoma, Ewing’s sarcoma and some other tumors in children and adults are able to express disialogangliside GD2. The introduction of anti-GD2 monoclonal antibodies into neuroblastoma treatment protocols has improved outcomes. Studies of the effectiveness of using anti-GD2 monoclonal antibodies in other tumors are also underway.In this review, we describe the main cellular and molecular processes occurring during passive anti-GD2 immunotherapy in pediatric tumors, as well as the factors that can affect them. We concluded that the leading role belongs to antibody-dependent cellular cytotoxicity realized by natural killers via the classical mechanism with the induction of caspase-dependent apoptosis, as well as macrophages, neutrophils through phagocytosis, trogocytosis and direct cytotoxicity. Efficient phagocytosis is promoted by expression of calreticulin by tumor cells and LRP1 receptor by phagocytes, while expression of CD47 by tumor cells and its interaction with SIRPα on phagocytes contribute to evasion of phagocytosis. In parallel, activation of T-cell adaptive immune response occurs. The use of granulocyte and granulocyte-macrophage colony-stimulating factors can enhance cytotoxicity. Addition of exogenous interleukin 2 does not improve the effectiveness of treatment, and the use of interleukins 15 and 21 enhances cytotoxicity in vitro, which requires clinical trials. Complement-dependent cytotoxicity probably does not affect the therapeutic efficacy of passive anti-GD2 immunotherapy. Tumor microenvironment and molecular features of immunocompetent cells can affect anti-GD2-mediated cytotoxicity, especially when used in combination with programmed cell death 1 (PD-1) inhibitors, thus, further study of this issue is especially relevant. Anti-GD2 monoclonal antibodies directly reduce the proliferative activity and induce apoptosis of tumor cells by inhibiting signaling pathways (mainly PI3K/Akt/mTOR), transcription factors, focal adhesion complexes, and integrins. Mechanisms for inducing mitochondria-dependent cell death, which has signs of apoptosis and necrosis, are also probable.